Comparative Proteomic Analysis of Membrane Vesicles from Clinical C. acnes Isolates with Differential Antibiotic Resistance - Jiang M; Fan X; Jiang Z; Chen H; Liu Y; Yu T; Huang Q; Ma Y (Dove Medical Press, 2022)
Min Jiang,* Xiaoyao Fan,* Ziqi Jiang, Huyan Chen, Ye Liu, Tianze Yu, Qiong Huang, Ying Ma Department of Dermatology, Huashan Hospital, Fudan University, Shanghai, 200040, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiong Huang; Ying Ma, Department of Dermatology, Huashan Hospital, Fudan University, No. 12 Wulumuqizhong Road, Shanghai, 200040, People's Republic of China, Email blueqiong1972@163.com; alle_ma@163.comPurpose: Cutibacterium acnes (C. acnes) is closely associated with the pathogenesis of acne, and antibiotics targeting C. acnes have been widely used for decades. However, antibiotic resistance has been increasing rapidly. Membrane vesicles (MVs) have been found to play important roles in antibiotic resistance in some bacteria. We aimed to explore the mechanism of antibiotic resistance and the virulence components within C. acnes-derived MVs.Materials and Methods: We isolated clinical C. acnes strains from the lesions of acne patients who were sensitive or resistant to the antibiotics erythromycin and clindamycin. We analyzed the proteome of MVs from four sensitive C. acnes isolates and three resistant isolates by LC-MS/MS.Results: We identified 543 proteins within the MVs of clinical C. acnes strains. Several lipases, NlpC/P60, CAMP factor, and Hta domain protein were detected as virulence factors in the C. acnes-derived MVs. The levels of two lipases and FtsZ were significantly higher in resistant C. acnes-derived MVs compared with sensitive strains (p < 0.05).Conclusion: According to the implications of this study, improper antibiotic use might not only increase antibiotic resistance in C. acnes but could also further alter the cutaneous lipid composition and aggravate host inflammation, thus resulting in worse clinical manifestations in acne patients. This study re-emphasizes that the improper use of antibiotics should be treated more seriously in clinical practice. Furthermore, to combat multidrug resistance in C. acnes, this study suggests that FtsZ inhibitors could be useful.Keywords: Cutibacterium acnes, antibiotics, FtsZ inhibitor, membrane vesicles